Image-Guided Intratumoral Delivery of Immunotherapeutics in Gastrointestinal Malignancies - Qiao, Yang; Sheth, Rahul A.; Tam, Alda (Digestive Disease Interventions, 2021)
Intratumoral (IT) administration of immunotherapy is a promising treatment strategy under clinical development for gastrointestinal malignancies. Due to its targeted nature, IT immunotherapies can generate regional proinflammatory microenvironments that result in the focal recruitment of tumor-specific immune cells. Precision targeting of tumors via IT immunotherapy injection theoretically produces a more robust immune response to the treated tumor itself and to distant metastatic tumors that share tumor-specific antigens with those of the treated tumor, while also minimizing the priming of the adaptive immune system to nonspecific antigens. Diverse arrays of IT immunotherapeutic agents including but not limited to lyophilized bacteria, viral vectors, cellular-based agents, molecules, and peptides, both as monotherapies and in combination with systemic immunotherapies, are in various stages of preclinical and clinical development. In this review, we summarize the current state of the art for IT immunotherapy and highlight potential future directions and their relevance to image-guided interventionalists.
Keywords: immunotherapy; intratumoral injection; GI malignancy; abscopal effect